Optimalisasi Strategi Bisnis E-Commerce Berbasis Model Integratif TAM-TTF: Analisis Penerimaan dan Kesesuaian Teknologi - Nurhafidah; Fadiyah Adiyah Yusuf; Muhammad Rispan Affandi; Tri Susilowati (Academic Bright Collaboration, 2025)
The development of technology in recent years has been very rapid, one of the results is the development of a buying and selling transaction system known as e-Commerce. Although it provides more benefits compared to traditional shopping methods, the development of online shopping in Indonesia has experienced various obstacles, including the low public awareness of using online shopping websites as a means of making buying and selling transactions and various other obstacles. This study will use a combination model between the TAM model and the task-technology fit (TTF) model that has been modified according to online shopping problems. The TTF model aims to measure the ability of information technology to support the completion of a task. The combination model will be analyzed using the Structural Equation Modeling (SEM) method. From the results of data processing using AMOS 6.0 software, it was found that the latent variable perceived ease of use did not affect the acceptance of online shopping technology. In addition, the results also show that the latent variables that significantly influence the actual use of online shopping technology are the latent variable perceived usefulness which influences the latent variable actual use by 1.095 and the latent variable task-technology fit which influences the latent variable actual use by 1.1653.